Hypergonadotropic hypogonadism: looking beyond ovarian senescence - Vatsa, Richa; Suri, Vanita; Choudahary, Neelam; Arora, Aashima; Sharma, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Gonadotropin resistant ovary syndrome (GROS) is a rare cause of primary infertility where ovarian reserve is present but they fail to respond to gonadotropin stimulation. This condition can be easily confused with premature ovarian insufficiency (POI) if thorough workup is not done as in both the cases serum FSH is high, but ovarian reserve is normal in GROS and low or absent in POI. So, we are presenting this case of GROS. A 28-year-old lady presented with oligomenorrhoea since menarche and primary infertility. On workup her serum FSH and LH levels were markedly elevated, serum estradiol was normal. Markers of ovarian reserve, ante Mullerian hormones (AMH) and antral follicle count (AFC), were normal. Her autoantibody assay was also normal. She did not respond to stimulation with high doses of gonadotropins (uHMG). Hypergonadotropic hypogonadism is not always POI. We should not miss diagnosis of GROS where it is possible to have own biological child by in vitro maturation of immature oocytes, whereas in POI donor oocyte is the only fertility option.